Road safety: embedded observers for estimation of vehicle's vertical tyre forces. (9th July 2012) - Doumiati, Moustapha; Charara, Ali; Victorino, Alessandro; Lechner, Daniel
Preventing car accidents using vehicle control systems requires input data concerning vehicle dynamic parameters. Unfortunately, some parameters, like the tyre-road contact forces that have a major impact on vehicle dynamics, are difficult to measure in a car. Therefore, this data must be estimated. In this context, this study presents an estimation process for load transfer and wheel-ground contact vertical forces. The proposed method is based on Kalman filter techniques and on the dynamic response of a vehicle instrumented with currently available standard sensors. Experimental results carried out using an experimental car show the effectiveness of the proposed approach.